Factors associated with candiduria and related mortality - Paul, Navin; Mathai, Elizabeth; Abraham, O.C.; Michael, Joy S.; Mathai, Dilip (The Journal of infection, 2007)
Although candiduria and bacteriuria have many attributes in common, little data is available regarding factors associated specifically with candiduria. Despite the high mortality in subjects with candiduria, factors associated with such mortality have not been studied. We undertook a single-center case–control study to evaluate factors associated with candiduria over a 10.5 month period. Cases and controls were prospectively recruited from hospitalized subjects with candiduria and bacteriuria, respectively. A subgroup analysis was performed to identify factors associated with mortality following candiduria. Among 145 subjects with candiduria, Candida tropicalis (30.5%) and other non-albicans species accounted for 71% of isolates. Among them, clinical characteristics and associations were studied among 80 hospitalized subjects. Prior antimicrobial use was documented in 92% with candiduria, with cephalosporins used most commonly. Independent associations with candiduria were demonstrated for use of antimicrobial agents in the preceding 30 days (odds ratio (OR) 8.1; 95% confidence interval (CI) 2.1–31.9) and plasma glucose >180 mg/dL (OR 3.1; 95% CI 1.1–9.1). Death occurred among 21 (26.2%) subjects with candiduria. Factors associated with death included use of urinary diversion devices (OR 8.8; 95% CI 1.1–70.5), ≥2 classes of antimicrobials (OR 4.1; 95% CI 1.2–13.9), intensive care (OR 3.3; 95% CI 1.1–9.3), and renal failure (OR 2.9; 95% CI 1.1–8.2). Many risk factors traditionally linked to candiduria may be associated with urinary tract infections in general. Factors which predicted occurrence of candiduria, as opposed to bacteriuria, included prior use of antimicrobial agents and elevated plasma glucose. Since factors found to have associations with death in candiduria were those expected in seriously ill patients, the high mortality may be a function of the severity of underlying diseases.